1969
DOI: 10.1530/acta.0.0610607
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Progesterone in Pregnancy Measured by a Rapid Competitive Protein Binding Technique

Abstract: Plasma levels of progesterone* were measured during normal human pregnancy by a sensitive and rapid competitive protein binding technique. During the first half of gestation 440 determinations in 321 women and in the second half of gestation, 209 determinations in 160 women were performed. The average plasma level of progesterone in the 5th week of gestation was 24.8 \ m=+-\7.3 (s) ng/ml which is above the normal range of the luteal plateau of the menstrual cycle (10\p=n-\20 ng/ml). Between the 5th and the 9th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
1

Year Published

1973
1973
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(32 citation statements)
references
References 14 publications
(16 reference statements)
5
26
1
Order By: Relevance
“…The values of serum progesterone in this study are similar to the plasma values reported by Johansson using a similar method (Johansson, 1969), and are comparable to the values obtained by gas liquid chromatography (Yannone, 1968) and the double isotope derivative assay (Weist, 1967). The results also correspond to the findings of earlier workers who employed a chemical method (Short, 1958;Greig et al, 1962).…”
Section: Sensityvity Specificity and Accuracysupporting
confidence: 90%
See 2 more Smart Citations
“…The values of serum progesterone in this study are similar to the plasma values reported by Johansson using a similar method (Johansson, 1969), and are comparable to the values obtained by gas liquid chromatography (Yannone, 1968) and the double isotope derivative assay (Weist, 1967). The results also correspond to the findings of earlier workers who employed a chemical method (Short, 1958;Greig et al, 1962).…”
Section: Sensityvity Specificity and Accuracysupporting
confidence: 90%
“…Several publications have described the assay of serum and plasma progesterone (Szarka, 1940;Short, 1958;Greig et al, 1962;Neil et al, 1967;Weist, 1967;Yannone, 1968;Johansson, 1969;Rubin et al, 1970;Murphy, 1971). Clinical and research applications for plasma progesterone determinations have been suggested (Johansson, 1969).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From the 9th to the 32nd week of gestation the plasma level of progesterone increased from 16.7 § 7.4 to 125.2 § 37.9 ng/ml. During the last 8 weeks [25].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma progesterone concentrations in women range from 30 to 450 nM depending on reproductive state (26), and the actions reported here were observed with progesterone in this range. -Receptor ligands have profound effects on function in the brain as well as the heart (19,21,35).…”
Section: Discussionmentioning
confidence: 48%